Targeting Autophagy Facilitates T Lymphocyte Migration by Inducing the Expression of CXCL10 in Gastric Cancer Cell Lines - Meng, Qingyuan; Zhang, Yihong; Hu, Liangbiao George (Frontiers in Oncology, 2020)
Autophagy is a type of cellular catabolic degradation process that occurs in response to nutrient starvation or metabolic stress, and is a valuable resource for highly proliferating cancer cells. Autophagy also facilitates the resistance of cancer cells to antitumor therapies. However, the involvement of autophagy in regulating CXCL10 expression in gastric cancer (GC) cells and T lymphocyte migration remains unclear. In this study, we aimed to investigate the effect of autophagy inhibition on CXCL10 expression and T lymphocyte infiltration in GC and elucidate the underlying mechanism. Analysis of public databases revealed a positive correlation between CXCL10 expression and both prognosis of patients with GC and the expression profile of T lymphocyte markers in the GCs. Chemotaxis and spheroid infiltration assays revealed that CXCL10 induced T lymphocyte migration and infiltration into GC spheroids, an in vitro three-dimensional cell culture model. In addition, in vitro autophagy inhibition in GC cells increased CXCL10 expression under both normal and hypoxic culture conditions. Further investigation on the underlying mechanism showed that in vitro autophagy inhibition suppressed the JNK signaling pathway and further enhanced CXCL10 expression in GC cells. Collectively, our results provide novel insights for understanding the role of autophagy in regulation of intra-tumor immunity.